PRODUCTION RESPONSE TO PRICES IN THE COCONUT INDUSTRY OF PAPUA NEW GUINEA - N. T M. H. De Silva; L. J Kiele; A. F. Lagap (International Coconut Community, 1987)
Coconut is one of the first plantation crops of Papua New Guinea. In 1922‑23 coconut made up 90 percent of exports and in 1950 it contributed 69 percent of the export earnings (Sackett and Williamson, 1977). Area under the crop is about 265,000 hectares or 0.6 percent of the total land area in the country (Charles, 1980, Turner, 1985). Relatively lower copra prices which prevailed especially in 1970s, the escalating cost of production coupled with Government policies aimed towards the diversification of country's export base have primarily resulted in copra becoming the 3rd(l) export earner of PNG. These changes nevertheless have not given rise to any marked decline in the copra production. What seems to have occurred is that the value of exports from other tree crop industries have exceeded the export value of copra.